2017
DOI: 10.1212/nxi.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of serum aryl hydrocarbon receptor agonists in MS

Abstract: Objective:Several factors influence the clinical course of autoimmune inflammatory diseases such as MS and inflammatory bowel disease. Only recently, the complex interaction between the gut microbiome, dietary factors, and metabolism has started to be appreciated with regard to its potential to modulate acute and chronic inflammation. One of the molecular sensors that mediates the effects of these environmental signals on the immune response is the aryl hydrocarbon receptor (AHR), a ligand-activated transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 47 publications
5
43
0
Order By: Relevance
“…While metabolomics analyses have identified alterations in multiple metabolic processes in MS, these techniques have not been previously applied to pediatric MS and have not studied the tryptophan pathway as a whole 30. Reduced plasma levels of Trp and some of its metabolites have been reported in adult MS patients compared to healthy subjects and dynamic modulation of some of these metabolites in the course of the disease has been described,13, 31 but the study of Trp metabolism in the risk of MS and disease activity and severity is novel.…”
Section: Discussionmentioning
confidence: 99%
“…While metabolomics analyses have identified alterations in multiple metabolic processes in MS, these techniques have not been previously applied to pediatric MS and have not studied the tryptophan pathway as a whole 30. Reduced plasma levels of Trp and some of its metabolites have been reported in adult MS patients compared to healthy subjects and dynamic modulation of some of these metabolites in the course of the disease has been described,13, 31 but the study of Trp metabolism in the risk of MS and disease activity and severity is novel.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that AHR agonistic activity varies during the course of inflammatory diseases such as MS and inflammatory bowel disease (IBD), suggesting that changes in circulating AHR agonists reflect alterations in the commensal flora, uptake, degradation or metabolism of physiological AHR agonists 4 , 7 , 8 . Thus, the quantification of AHR agonists is of clinical interest.…”
Section: Discussionmentioning
confidence: 99%
“…HEK293, HepG2, and HEPA1 cells were used in the transient transfection system, as previously described 7 , 8 . In brief, 15,000 cells per well were plated in 96 well flat bottom plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Moreover, serum levels of indoles and its metabolites are decreased in patients with MS. 71 However, a more recent study suggests a differential mechanism of regulation: AHR agonistic activity is increased during relapse episodes of MS and decreased during remission. 72 When discussing the role of nutrients in MS, we should carefully take into account not only a direct immunomodulatory role of diet but also its associated effects on microbiota composition and the development of obesity.…”
Section: Dietary Factorsmentioning
confidence: 99%